Business Model Enhancement to Belibu Freshmart’ Sustainability in Organic Industry - Marcellina Amanda Devina; Yos Sunitiyoso (AIBPM Publisher, 2021)
Belibu Freshmart is a one-stop shopping store that provides organic and healthy products in Bandung, West Java, Indonesia. Currently, Belibu Freshmart faces the problem with the fluctuated sales and how to survive doing their business, also planning for its future. For a company, business sustainability is essential to running their business in the long term. This research will examine which factors support Belibu Freshmart’s sustainability. This research aims to analyze the driving forces regarding factors that could affect the business and present strategic recommendations on ways forward within the organic market in Bandung with the purpose of business sustainability. Start with business issues exploration using a fishbone diagram and problem tree analysis built from a customer survey and internal discussions. This analysis is followed by internal (VRIO analysis and value chain analysis) and external (PESTLE model and Porter’s 5 Forces) condition analysis regarding the business. Then got the results by using SWOT analysis, TOWS analysis, and Triple Layered Business Model Canvas (TLBMC) that integrated with the Circular Model Economy to build sustainable business models.